1986
DOI: 10.1016/0014-5793(86)81501-0
|View full text |Cite
|
Sign up to set email alerts
|

Discrimination between transmembrane ion gradient‐driven and electron transfer‐driven ATP synthesis in the methanogenic bacteria

Abstract: As with Methanococcus voltae [(1986) FEBS Lett. 200, 177-180], ATP synthesis in Methanobacterium thermoautotrophicum (AH) can be driven by the imposition of a sodium gradient, but only in the presence of a counterion. Monensin (but not SF6847) inhibits this synthesis. Methanogenic electron transfer-driven ATP synthesis, however, is insensitive to the combination of these two ionophores. In M. voltae, 117 I~M diethylstilbestrol effectively inhibits both membrane potential-and sodium gradient-driven ATP synthesi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

1987
1987
2009
2009

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(8 citation statements)
references
References 25 publications
0
8
0
Order By: Relevance
“…This enzyme is evolutionarily distantly related to F 1 F O ATP synthase and has a different inhibitor profile. In the mid‐1980s, experimental data indicated an Na + ‐ATPase along with an H + ‐ATPase in the hydrogenotrophic archaeon Methanothermobacter thermautotrophicus based on differential inhibitor sensitivities (Al‐Marouq et al , 1986; Smigán et al , 1988). Studies performed with cells and vesicles of Methanosarcina mazei Gö1 also led to the suggestion that this species harbors two different ATP synthases, and inhibitor studies argued for a so far unidentified F 1 F O ATP synthase along with the well‐known A 1 A O ATP synthase (Becher & Müller, 1994).…”
Section: Introductionmentioning
confidence: 99%
“…This enzyme is evolutionarily distantly related to F 1 F O ATP synthase and has a different inhibitor profile. In the mid‐1980s, experimental data indicated an Na + ‐ATPase along with an H + ‐ATPase in the hydrogenotrophic archaeon Methanothermobacter thermautotrophicus based on differential inhibitor sensitivities (Al‐Marouq et al , 1986; Smigán et al , 1988). Studies performed with cells and vesicles of Methanosarcina mazei Gö1 also led to the suggestion that this species harbors two different ATP synthases, and inhibitor studies argued for a so far unidentified F 1 F O ATP synthase along with the well‐known A 1 A O ATP synthase (Becher & Müller, 1994).…”
Section: Introductionmentioning
confidence: 99%
“…On the basis of evidence that electron transfer-driven ATP synthesis in Methanococcus voltae is not dependent on a proton electrochemical gradient, a molecular scheme in which ATP synthesis is coupled directly to electron transfer has been proposed (10,25). Furthermore, the M. voltae ATPase is not considered to function physiologically as an ATP synthase; rather, it is believed to be involved in electrogenic sodium translocation (1,8).…”
mentioning
confidence: 99%
“…Correspondence address: P. ~mig~ifl, Institute of Animal Physiology, Slovak Academy of Sciences, 900 28 Ivanka pri Dunaji, Czechoslovakia been demonstrated [12]. On the basis of these observations the existence of an electrogenic sodium ion-translocating ATPase in these organisms has been postulated [11,12]. The exact role of this electrogenic Na+-translocating ATPase is not known but it has been suggested that under physiological conditions it might drive the exit of sodium ions from the cells of methanogenic bacteria.…”
Section: Methanobacterium Thermoautotrophicum Hasmentioning
confidence: 99%